Desain Sistem Informasi Reservasi Ranap Guna Menunjang Tata Kelola Klinis Ranap Berbasis Web - Sulastri, Sania; Syahidin, Yuda; Suryani, Ade Irma (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2024)
Technological advances, especially in the health sector, continue to develop every year. One of them is in terms of hospital information systems and health services. The wide range of hospital services, of course, will cause complex problems to arise. One of the problems that arise is that services at the hospital in making inpatient reservations still use a manual system via telephone which is less effective for registration officers with the admin of the inpatient room regarding the availability of inpatient rooms so that patients spend longer waiting. The purpose of this research is to create a web-based inpatient reservation information system to make it easier for officers to make reservations and get information about the availability of inpatient rooms for patients. So that the administrative process can obtain room information more accurately and effectively. The software development method used is prototype. Making information system design models is made using Xampp with PHP and MySQL database systems and the system is tested with blackbox testing. The results of the information system created can assist hospital staff in providing maximum service by reporting inpatient room information data.